Loop Electrosurgical Excision Procedure under Propofol Intravenous Anesthesia Combined with Nano-Silver Gel in the Treatment of Cervicitis: Loop Electrosurgical Excision Procedure under Propofol Intravenous Anesthesia - Liu, Zhilin; Zou, Xin; Sun, Xiaopeng; Fan, Wenjie (Cellular and Molecular Biology, 2022)
It was aimed at the therapeutic value of loop electrosurgical excision procedure (LEEP) under propofol intravenous anesthesia combined with nano-silver gel in chronic cervicitis. 100 patients with chronic cervicitis were selected and randomly divided into the control group with 50 cases (LEEP under intravenous anesthesia with fentanyl) and the experimental group with the other 50 cases (LEEP under propofol intravenous anesthesia combined with the nano-silver gel). It was suggested from the results that the mean arterial pressure (MAP) and heart rate (HR) (76.88±5.65mmHg, 75.45±5.06beats/min) of patients in the experimental group at T1 time were better than those of the control group (83.76±5.43mmHg, 68.31±5.28beats/min). Visual analogue scale (VAS) (1.85±0.73 points), onset time of anesthesia (0.56±0.21min), time to open eyes (2.45±1.38min) and time of consciousness recovery (5.22±1.42min) were all lower than those of the control group (2.83±0.79 points, 0.93±0.25min, 4.33±1.45min, and 7.15±1.34min, respectively). The incidence of adverse reactions, the effective rate of treatment, the time of wound healing, and the incidence of complications (6%, 94%, 23.83±2.05 days, and 6%, respectively) were all better than those of the control group (24%, 70%, 29.25±2.16 days, and 6%) (P<0.05). All in all, intravenous anesthesia with propofol was beneficial to perform LEEP better, and the combination of LEEP combined with nano-silver gel had an important value in the treatment of chronic cervicitis and was worthy of clinical promotion.